PENERAPAN MODEL PEMBELAJARAN COURSE REVIEW HORAY PADA MATERI SISTEM PENCERNAAN MANUSIA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V MIN 8 PIDIE - Junaidah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2020)
The purpose of this study was to determine the application of the Course Review Horay learning model to the material of the human digestive system in V MIN 8 Pidie students. The data collection techniques used are observation, interviews, tests, and field notes. From the results of the study found that in the first cycle the average value obtained by students is 49.23 while the classical completeness obtained by 23%. In cycle II the average value is 65.38, while the classical completeness obtained 69%. In the third cycle the average value is 77, 69 and the classical completeness obtained by students is 100%. Thus it can be concluded that the Application of Course Review Horay Learning Model on the Material of the Human Digestive System can Improve Student Learning Outcomes of Class V MIN 8 Pidie successfully.